Development e-TBL to Analyze Critical Thinking Skills and Problem Solving in Learning of Substance and Characteristics (Universitas Negeri Semarang, 2020)
Electronic Task Based Learning (e-TBL) is learning by giving assignments to students assisted by electronic media so that students are more active. In SMPIT Izzatul Islam (SMPIT Izzis) Getasan e-TBL is not yet available to analyze critical thinking skills and problem solving on learning substance and characteristics. This study aims to develop a valid and reliable e-TBL to analyze critical thinking skills and problem solving in learning substance and characteristics and to find out the responses of users after using e-TBL as a result of development. Type of this research is the research and development of the 4D model. The subjects of this study were students of grade 8 SMPIT Izzis. A limited test was conducted to determine the readability of e-TBL, the feasibility of e-TBL, and user responses to e-TBL conducted with a questionnaire sheet that tested its validity and reliability. The data analysis technique used in this study was quantitative descriptive. Based on research results, the development of e-TBL is feasible to use because it is valid and reliable. Responses from users also show that the development of e-TBL is feasible to be used to analyze critical thinking skills and problem solving on learning substance and characteristics.